Development of Vaccines for Chikungunya Fever - Erasmus, Jesse H. (J Infect Dis, 2016)
Chikungunya fever, an acute and often chronic arthralgic disease caused by the mosquito-borne chikungunya virus (CHIKV), has reemerged since 2004 to cause millions of cases. Because CHIKV exhibits limited antigenic diversity and is not known to be capable of reinfection, a vaccine could serve to both prevent disease and diminish human amplification during epidemic circulation. Here, we review the many promising vaccine platforms and candidates developed for CHIKV since the 1970s, including several in late preclinical or clinical development. We discuss the advantages and limitations of each, as well as the commercial and regulatory challenges to bringing a vaccine to market.